2020
DOI: 10.1038/s41598-020-58567-6
|View full text |Cite
|
Sign up to set email alerts
|

Recent magmatism drives hydrocarbon generation in north-east Java, Indonesia

Abstract: Conventional studies of petroleum basins associate oil generation with the gradual burial of organic-rich sediments. These classical models rely on the interplay between pressure, temperature, and the time required for organic matter transformation to oil and gas. These processes usually occur over geological timescales, but may be accelerated by rapid reactions when carbon-rich sediments are exposed to migrating magmatic fluids. The spectacular Lusi eruption (north-east Java, Indonesia) is the surface express… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 68 publications
0
3
0
1
Order By: Relevance
“…Numerous scientific studies from different disciplines have shown that this eruption is connected and fed at depth by the neighboring volcanic complex (Fallahi et al., 2017; Inguaggiato et al., 2018; Zaputlyaeva et al., 2019). The migration of magmatic and hydrothermal fluids into the deep organic‐rich source rock deposits of the basin, triggered thermometamorphic reactions and fluids overpressure at depth (Malvoisin et al., 2018; Mazzini et al., 2012; Svensen et al., 2018; Zaputlyaeva et al., 2020). These fluids are ultimately released at the Lusi crater with impressive geysering activity at the surface (Karyono et al., 2017; Lupi et al., 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous scientific studies from different disciplines have shown that this eruption is connected and fed at depth by the neighboring volcanic complex (Fallahi et al., 2017; Inguaggiato et al., 2018; Zaputlyaeva et al., 2019). The migration of magmatic and hydrothermal fluids into the deep organic‐rich source rock deposits of the basin, triggered thermometamorphic reactions and fluids overpressure at depth (Malvoisin et al., 2018; Mazzini et al., 2012; Svensen et al., 2018; Zaputlyaeva et al., 2020). These fluids are ultimately released at the Lusi crater with impressive geysering activity at the surface (Karyono et al., 2017; Lupi et al., 2018).…”
Section: Introductionmentioning
confidence: 99%
“…This part of the island is also characterized by numerous diapirs and seismic profiles show that some of these have undergone eruption and subsidence (Istadi et al., 2009; Miller & Mazzini, 2018; Moscariello et al., 2018). Several geochemical (Inguaggiato et al., 2018; Mazzini et al., 2012, 2018; Sciarra et al., 2018; Zaputlyaeva et al., 2019), geological (Mazzini et al., 2021; Moscariello et al., 2018; Samankassou et al., 2018; Zaputlyaeva et al., 2020), numerical (Collignon, Schmid, et al., 2018; Lupi et al., 2013, 2014; Svensen et al., 2018) and geophysical (Karyono et al., 2017; Lupi et al., 2018; Mauri, Husein, Mazzini, Irawan, et al., 2018, Mauri, Husein, Mazzini, Karyono, et al., 2018; Panzera et al., 2018; Obermann et al., 2018; Osorio Riffo et al., 2021) studies contributed to the better understanding of the subsurface structure of Lusi. However, to date a clear picture of the Lusi shallow plumbing system is still missing.…”
Section: Introductionmentioning
confidence: 99%
“…Berbeda dengan Zona Selatan, nilai 𝑏 untuk Zona Utara pada Gambar 4(a) hampir mendekati 1. Argumen terbaik adalah aktivitas kegempaan di wilayah utara Jawa Timur banyak dipengaruhi oleh Sesar Kendeng sebagai perpanjangan dari busur belakang Flores (Koulali et al, 2016;Koulali et al, 2017), Sesar Pasuruan (Marliyani et al, 2019) dan busur Sunda Modern yang terbentuk pada jaman kwatier yang lebih muda dari jaman tersier (Soeria-Atmadja et al, 1994;Setijadji et al, 2006;Smyth et al, 2008;van Gorsel, 2018;Cholifah et al, 2020;Zaputlyaeva et al, 2020).…”
Section: Kurva Fmdunclassified
“…Mercury speciation determines how (im)mobile Hg might be during erosion (Manceau et al., 2018) or upon heating, such as during hydrocarbon formation, production and burning (Yudovich & Ketris, 2005), but also soils subjected to intense forest fires (Biswas et al., 2007), and sediments near intrusive and eruptive volcanic activity (Chen et al., 2022; Liu et al., 2022; Svensen et al., 2023; Zaputlyaeva et al., 2020). It is difficult to gauge the importance of geological Hg fluxes from any of these potential sources without knowledge of Hg speciation in (sedimentary) rocks.…”
Section: Introductionmentioning
confidence: 99%